A fine‐tuned composition of protein nanofibrils yields an upgraded functionality of displayed antibody binding domains. Issue 6 (8th May 2017) - Schmuck, Benjamin; Sandgren, Mats; Härd, Torleif
Abstract: Elevated performance of instruments and electronic devices is frequently attained through miniaturization of the involved components, which increases the number of functional units in a given volume. Analogously, to conquer the limitations of materials used for the purification of monoclonal antibodies and for the sensitivity of immunoassays, the support for capturing antibodies requires miniaturization. A suitable scaffold for this purpose are cross‐β structured protein nanofibrils, as they offer a superior surface area over volume ratio and because manipulation can be implemented genetically. To display the antibody binding Z‐domain dimers (ZZ) along the surface of the fibrils and grant maximal accessibility to the functional units, the N‐terminal fragments of the fibrillating translation release factor Sup35 or ureidosuccinate transporter Ure2, both from Saccharomyces cerevisae, are simultaneously fibrillated with the chimeric‐proteins Sup35‐ZZ and ZZ‐Ure2, respectively. Optimization of the fibril composition yields a binding capacity of 1.8 mg antibody per mg fibril, which is a binding capacity that is almost 20‐fold higher, compared to the commercially available affinity medium gold standard, protein A sepharose. This study lifts the craft of nanofibril functionalization to the next level, and offers a universal framework to improve biomaterials that rely on the display of functional proteins or enzymes. Abstract : A proof‐of‐concept material captures antibodies along a matrix consisting of cross‐β structured protein nanofibrils and binds 20‐fold more than any other commercially available material. The scaffold serves as a universal framework for efficient nanofibril functionalization and is potentially suitable for the purification of monoclonal antibodies or to increase the sensitivity of immunoassays.